2019
DOI: 10.3389/fgene.2019.00616
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetics of Cytomegalovirus Pathogenesis

Abstract: Human cytomegalovirus (HCMV) is a ubiquitous herpes virus (human herpes virus 5) with the highest morbidity and mortality rates compared to other herpes viruses. Risk groups include very young, elderly, transplant recipient, and immunocompromised individuals. HCMV may cause retinitis, encephalitis, hepatitis, esophagitis, colitis, pneumonia, neonatal infection sequelae, inflammatory, and age-related diseases. With an arsenal of genes in its large genome dedicated to host immune evasion, HCMV can block intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 126 publications
(133 reference statements)
0
42
0
Order By: Relevance
“…Similarly, also in the case of HCMV the role of host genetics in immune response to the virus was revealed and a large collection of associated genes was identified eg. TLRs, NKG2D, PD-1, IFNG, IL-6 just to name a few (reviewed in [262]). The clinical course of HSV-1 infection can be modified by MHC class I allotypes (B*18, C*15, and the group of alleles encoding A19), the high-affinity receptor/ligand pair KIR2DL2/HLA-C1, and the CD16A-158V/F dimorphism.…”
Section: Virus Reactivationmentioning
confidence: 99%
“…Similarly, also in the case of HCMV the role of host genetics in immune response to the virus was revealed and a large collection of associated genes was identified eg. TLRs, NKG2D, PD-1, IFNG, IL-6 just to name a few (reviewed in [262]). The clinical course of HSV-1 infection can be modified by MHC class I allotypes (B*18, C*15, and the group of alleles encoding A19), the high-affinity receptor/ligand pair KIR2DL2/HLA-C1, and the CD16A-158V/F dimorphism.…”
Section: Virus Reactivationmentioning
confidence: 99%
“…In order to clarify the implications of the virus on transplant outcome, the genetic risk factors of CMV infection have been considered. Thus, some polymorphisms located in genes involved in immune response have been studied (22)(23)(24)(25), including the interferon gamma (IFNG) gene (26,27). IFN-γ is a cytokine of the Th1 subset, which has been associated with the inflammatory process and kidney injury, and it plays a critical role in the immune response against viral infection (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…The genes encoding TLRs are extremely polymorphic and several studies have reported the association between single nucleotide polymorphisms (SNPs) in the TLRs and enhanced susceptibility and severity to systemic infections (Schroder and Schumann, 2005;Netea et al, 2012;Sezgin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%